2010
DOI: 10.1002/jor.21153
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated aging of intervertebral discs in a mouse model of progeria

Abstract: Intervertebral disc degeneration (IDD) is a common and debilitating disorder that results in reduced flexibility of the spine, pain, and reduced mobility. Risk factors for IDD include age, genetic predisposition, injury, and other environmental factors such as smoking. Loss of proteoglycans (PGs) contributes to IDD with advancing age. Currently there is a lack of a model for rapid investigation of disc aging and evaluation of therapeutic interventions. Here we examined progression of disc aging in a murine mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(114 citation statements)
references
References 46 publications
(49 reference statements)
8
105
1
Order By: Relevance
“…The syndrome is characterized by accelerated aging of virtually all organ systems, all driven by failure to repair stochastic endogenous DNA damage. A murine model of XFE progeroid syndrome, Ercc1 -/Δ mice, have about 10% of the normal amount of ERCC1 protein and spontaneously develop progressive, degenerative changes that correlate strongly with natural aging (43)(44)(45)(46)(47). Thus, Ercc1 -/-mice, which have a complete absence of ERCC1 protein, and Ercc1 -/Δ mice offer a unique opportunity to investigate the mechanism by which one type of cellular damage promotes aging and whether NF-κB plays a pivotal role.…”
Section: Introductionmentioning
confidence: 99%
“…The syndrome is characterized by accelerated aging of virtually all organ systems, all driven by failure to repair stochastic endogenous DNA damage. A murine model of XFE progeroid syndrome, Ercc1 -/Δ mice, have about 10% of the normal amount of ERCC1 protein and spontaneously develop progressive, degenerative changes that correlate strongly with natural aging (43)(44)(45)(46)(47). Thus, Ercc1 -/-mice, which have a complete absence of ERCC1 protein, and Ercc1 -/Δ mice offer a unique opportunity to investigate the mechanism by which one type of cellular damage promotes aging and whether NF-κB plays a pivotal role.…”
Section: Introductionmentioning
confidence: 99%
“…IDD pathogenesis is affected by various factors including genes, life styles, biophysics, and other chronic diseases, making it one complicated and refractory disease that severely affect patient's health and life quality [11]. In clinics, major approaches for treating IDD include surgery, conservative treatment, cell therapy or gene therapy, all of which may not achieve satisfactory results [12].…”
Section: Discussionmentioning
confidence: 99%
“…6,7 The development of IDD is related to genetic predisposition, excessive load, smoking, and the natural aging process. 8,9 Many studies on the cellular mechanisms of IDD have demonstrated the importance of maintaining extracellular matrix homeostasis, striving for a balance between the synthesis and the catabolism of its components. 10,11 However, natural history, as well as the biological mechanisms that lead to IDD, still have gaps to be filled.…”
Section: Introductionmentioning
confidence: 99%